Primary health care to patients with gout - Maria Vladimirovna Sklyanova; A N Kalyagin (Современная ревматология, 2012)
Gout is a systemic tophaceous disease that is becoming more and more prevalent. If untreated or poorly managed, gout can result in disability. The possible reason for inadequate gout control may be that the primary care physicians are unaware of diagnostic criteria and clinical guidelines for the management of these patients and diagnostic errors. Objective: to estimate the level of gout knowledge in primary care physicians. Subjects and methods. Fifty Irkutsk local therapists were questioned. A specially developed anonymous questionnaire included items on sex, age, work experience, and the principles of gout diagnosis and treatment. Results. Only 42% of the therapists know that the gold standard for diagnosis of gout is identification of monosodium urate crystals by polarizing microscopy. Only 6% of the therapists use the Wallace classification criteria for the early diagnosis of gout. 56 % of the physicians consider it possible to prescribe allopurinol in the acute period of the disease 26% think that allopurinol intake can be stopped after normouricemia is achieved; 10% of the physicians do not prescribe allopurinol for gout patients. These widespread errors lead to worsening arthritis and a negative attitude of patients towards allopurinol treatment in future. Conclusion. The findings suggest that the level of gout knowledge should be increased in primary care physicians.